2005
DOI: 10.1111/j.1469-8137.2004.01297.x
|View full text |Cite
|
Sign up to set email alerts
|

Preferential elimination of repeated DNA sequences from the paternal, Nicotiana tomentosiformis genome donor of a synthetic, allotetraploid tobacco

Abstract: Summary• Nicotiana tabacum (tobacco, 2 n = 4 x = 48) is a natural allotetraploid combining two ancestral genomes closely related to modern Nicotiana sylvestris and Nicotiana tomentosiformis . Here we examine the immediate consequences of allopolyploidy on genome evolution using 20 S 4 -generation plants derived from a single synthetic, S 0 plant made by Burk in 1973 (Th37).• Using molecular and cytogenetic methods we analysed 14 middle and highly repetitive sequences that together total ≈ 4% of the genome.• Tw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

10
119
0
2

Year Published

2006
2006
2020
2020

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 135 publications
(131 citation statements)
references
References 72 publications
10
119
0
2
Order By: Relevance
“…The ascendancy of the B. rapa genome over B. oleracea has already been described by Chen and Pikaard (1997), who observed a nucleolar dominance of B. rapa rRNA genes in reciprocal crosses of synthetic oilseed rape. Directed parental genome modifications seem to be a recurrent feature of allopolyploid formation: in several synthetic allopolyploids (Song et al 1995;Adams et al 2004;Skalicka et al 2005), a bias toward one genome has been reported, frequently in favor of the maternal genome, suggesting that genome changes might by influenced by nucleocytoplasmic interactions. However, in our synthetic B. napus, the predominant gene expression pattern was of paternal origin and there was no bias in the cellular localization of proteins displaying nonadditive value.…”
Section: Discussionmentioning
confidence: 99%
“…The ascendancy of the B. rapa genome over B. oleracea has already been described by Chen and Pikaard (1997), who observed a nucleolar dominance of B. rapa rRNA genes in reciprocal crosses of synthetic oilseed rape. Directed parental genome modifications seem to be a recurrent feature of allopolyploid formation: in several synthetic allopolyploids (Song et al 1995;Adams et al 2004;Skalicka et al 2005), a bias toward one genome has been reported, frequently in favor of the maternal genome, suggesting that genome changes might by influenced by nucleocytoplasmic interactions. However, in our synthetic B. napus, the predominant gene expression pattern was of paternal origin and there was no bias in the cellular localization of proteins displaying nonadditive value.…”
Section: Discussionmentioning
confidence: 99%
“…Studies of genetic and epigenetic changes associated with polyploidization have been focused mostly on newly synthesized allopolyploid materials 1 (Song et al 1995;Liu et al 1998;Comai et al 2000;Ozkan et al 2001;Kashkush et al 2002;Madlung et al 2002Madlung et al , 2005He et al 2003;Kashkush et al 2003;Adams et al 2004;Wang et al 2004Wang et al , 2006Skalicka et al 2005;Albertin et al 2006;Lukens et al 2006). However, in allopolyploids, ploidy level per se is difficult to tease apart from many other variables, such as diverged suites of regulatory factors from different genomes.…”
mentioning
confidence: 99%
“…In these genomes, natural selection and stochastic processes govern the genetic fate of each paralog-fates that include redundancy, subfunctionalization, neofunctionalization, and gene silencing (Ohno 1970;Hughes and Hughes 1993;Force et al 1999;Lynch and Force 2000;Lynch et al 2001;Gu 2003). After allopolyploidization, interactions between the subgenomes derived from each ancestral species included exchange of chromosome segments (Moscone et al 1996;Skalická et al 2005), concerted evolution (Wendel et al 1995;Volkov et al 1999), recombination (Zwierzykowski et al 1998), and epistasis ( Jiang et al 2000). Restructuring can then alter the stoichiometry of protein interactions by modifying regulatory elements or changing gene copy number.…”
mentioning
confidence: 99%